Comparison of percutaneous transforaminal endoscopic discectomy and open lumbar discectomy for lumbar disc herniations: A systematic review and meta-analysis - Zhang, Jian; Gao, Yangyang; Zhao, Bin; Li, Haoyang; Hou, Xuening; Yin, Liqiang (Frontiers in Surgery, 2022)
Purpose: In order to compare the outcomes of percutaneous transforaminal endoscopic discectomy (PTED) and open lumbar discectomy (OLD) for lumbar disc herniation (LDH). Methods: The Pubmed, Cochrane Library, Web of Sience, Embase, Clinicaltrials.gov, CBM, CNKI, VIP, Wangfang databases were searched from inception to April, 2022 to collect the published studies about PTED versus OLD for treatment of LDH. The Revman 5.2 was used for data analysis. The primary outcomes were excellent rates, complication rates and reoperation rates. The secondary outcomes were length of incision, length of operation, length of hospital stay, and the amount of intraoperative blood loss. Results: A total of nine studies were included, of which, eight randomized controlled trials and one retrospective study involving 1,679 patients with LDH (755 patients for PTED, and 924 patients for OLD) were included. According to meta-analysis, there were no significant difference in excellent rates (odds ratio [OR] = 1.47, 95% confidence intervals [CI]: 0.94 to 2.28, P = 0.09), reoperation rates (OR = 0.96, 95% CI: 0.50 to 1.84, P = 0.90), length of operation (standardized mean differences [SMD] = -17.97, 95%CI: -54.83 to 18.89, P = 0.34), and the amount of intraoperative blood loss (SMD = -128.05, 95%CI: -258.67 to 2.57, P = 0.05), respectively. There were significant differences in complication rates (OR = 0.22, 95% CI: 0.14 to 0.33, P < 0.001), length of incision (SMD = -2.76, 95%CI: -2.88 to -2.65, P < 0.001), and length of hospital stay (SMD = -5.19, 95%CI: -5.36 to -5.01, P < 0.001), respectively. Conclusions: PTED can achieve better outcomes with respect to the complication rates, length of incision, and length of hospital stay compared with OLD.